2016
DOI: 10.1038/labinvest.2016.104
|View full text |Cite
|
Sign up to set email alerts
|

Apical membrane expression of distinct sulfated glycans represents a novel marker of cholangiolocellular carcinoma

Abstract: Intrahepatic cholangiocarcinoma (ICC) is the second most common primary liver neoplasm, followed by hepatocellular carcinoma. ICC can be further subclassified as (i) perihilar and (ii) peripheral types, the latter histologically resembling small-sized intrahepatic bile ducts, such as interlobular bile ducts, cholangioles/ductules and the canals of Hering. Cholangiolocellular carcinoma (CoCC), now classified by the World Health Organization as a subtype of combined hepatocellular-cholangiocarcinoma, is currentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 53 publications
1
22
0
Order By: Relevance
“…We also analyzed the mRNA levels of CHST4 in 34 different types of human tumors. Consistent with previous studies, we found that the expression of CHST4 mRNA was higher in cholangiocarcinoma (24), colon adenocarcinoma (18), and gastric adenocarcinoma (22), and we partially verified this conclusion immunohistochemically. We also found that tumor expression of CHST4 at the mRNA and protein level is only partially consistent.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We also analyzed the mRNA levels of CHST4 in 34 different types of human tumors. Consistent with previous studies, we found that the expression of CHST4 mRNA was higher in cholangiocarcinoma (24), colon adenocarcinoma (18), and gastric adenocarcinoma (22), and we partially verified this conclusion immunohistochemically. We also found that tumor expression of CHST4 at the mRNA and protein level is only partially consistent.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, in those with early-stage uterine corpus and cervical cancer, serum CHST4 expression was higher than that of cancer antigen 125 (CA125) and squamous cell carcinoma antigen (SCC) (21). CHST4 expression is also elevated in gastric cancer tissues (22), urothelial bladder carcinoma (23), cholangiolocellular carcinoma (24), and Opisthorchis viverrini (OV)-related intrahepatic cholangiocarcinoma (25), and the CHST4 promoter is hypermethylated in HBV-HCC (26). In gliomas, CHST4 was shown to have a high frequency of mutant alleles and amplifications and was related to poor prognosis (27).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed colocalization of MECA-79 (a cholangiocyte marker) and MUC1 on apical membrane of cholangiocytes with cholangial/ductular differentiation. Hence, CoCCs are also regarded as a subtype of peripheral-type iCC [110]. On the other hand, the most recent molecular research indicates that CoCCs are distinct biliary-derived entities associated with chromosomal stability and active TGF-β signalling, without any traits of the HCCs [111].…”
Section: Role Of Mucins In Hepatobiliary Carcinogenesismentioning
confidence: 99%
“…Cholangiocarcinoma (currently type 2 IPNB) is also anatomically classified into perihilar and distal types of iCC [95,96,121,124]. Hilar carcinoma (called Klatskin tumour) and peripheral CC can be distinguished among iCCs, with both previously noted to exhibit mucin production [95,110]. Both subtypes of iCC are thought to arise from topologically different IBDs [107].…”
Section: Role Of Mucins In Hepatobiliary Carcinogenesismentioning
confidence: 99%
“…In a previous study, CoCC did not exhibit mucin production, although ICC did (25). Immunohistochemically, luminal EMA expression and positive CD56 are observed in CoCC, whereas cytoplasmic EMA expression and negative CD56 expression are usually observed in ICC (26). The histopathological features of these tumors are described in Table II.…”
Section: Discussionmentioning
confidence: 99%